2019
DOI: 10.1007/s40995-019-00743-z
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dunford–Pettis Completely Continuous Like Operators

Abstract: In this article, the class of all Dunford-Pettis p-convergent operators and p-Dunford-Pettis relatively compact property on Banach spaces are investigated. Moreover, we give some conditions on Banach spaces X and Y such that the class of bounded linear operators from X to Y and some its subspaces have the p-Dunford-Pettis relatively compact property. In addition, if Ω is a compact Hausdorff space, then we prove that dominated operators from the space of all continuous functions from K to Banach space X (in sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several authors have found the study of T to be quite helpful. We mention the work of [6], [10], [8], [24], [14], [25], [3], [27], and [23]. In these papers it has been proved that if m is strongly bounded, then T : C(K, X) → Y is Dunford-Pettis, Dieudonné, unconditionally converging, strictly singular, strictly cosingular, weakly precompact, weakly p-compact, limited, pseudo weakly compact, Dunford-Pettis p-convergent if and only if its extension T : B(Σ, X) → Y has the same property.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have found the study of T to be quite helpful. We mention the work of [6], [10], [8], [24], [14], [25], [3], [27], and [23]. In these papers it has been proved that if m is strongly bounded, then T : C(K, X) → Y is Dunford-Pettis, Dieudonné, unconditionally converging, strictly singular, strictly cosingular, weakly precompact, weakly p-compact, limited, pseudo weakly compact, Dunford-Pettis p-convergent if and only if its extension T : B(Σ, X) → Y has the same property.…”
Section: Introductionmentioning
confidence: 99%